Currency hedging behavior for stock returns uncertainty in Ghana. Issue 48 (14th October 2022) - Bachori, Bartholomew Bilijo; Buabeng, Emmanuel; Sakyi, Daniel
ABSTRACT: This article investigates the dynamic interaction between stock market returns and exchange rate movement and their implication for portfolio risk management in Ghana. To do so, and considering the Covid-19 crisis, the Dynamic Conditional Correlation Multivariate GARCH estimation technique was employed on daily data for Ghana Stock Exchange (GSE) Composite Index and the Ghana Cedi to USD, Euro, and GBP exchange rates from 3 January 2012 to 26 November 2021. The results revealed that: (i) the GSE market has no significant exposure to the USD, Euro, and GBP exchange rates in the full sample and periods before the crisis but was significantly exposed to the Euro rates during the crisis, (ii) the returns on holding foreign currencies were relatively higher but riskier compared to returns on stocks for the full sample and periods before the crisis, and (iii) while the Euro rates act as the most efficient hedge currency for stock returns uncertainty the correlations between stock returns and exchange rate movement were generally low and therefore, forming a portfolio of stocks and currency pairs improved an investor's daily returns and risk. Based on the findings, relevant policy suggestions are offered to guide investors and policymakers.